Acceptable Morita Contexts for Semigroups. (1st July 2012) - Laan, Valdis
Abstract : This short note deals with Morita equivalence of (arbitrary) semigroups. We give a necessary and sufficient condition for a Morita context containing two semigroups S and T to induce an equivalence between the category of closed right S -acts and the category of closed right T -acts.